DIGITALISASI DESA SEBAGAI STRATEGI PEMBANGUNAN BERKELANJUTAN: KAJIAN LITERATUR REVIEW DENGAN PENDEKATAN SOCIETY-CENTERED - Mayyora, Restu; Ike Wanusmawatie (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The significant contribution of villages to national sustainable development has brought a new focus on development at the village level, so villages are also affected by the massive shift towards digitalization. This article examines the process of village digitalization in development efforts through a society-centered approach to understand that the study of digitalization development is not solely about infrastructure provision, but also about how the community is involved. The method used was a literature review of previous research studies sourced from scientific journals relevant to village digitalization, sustainable development, and society. The results of this article's review found that the presence of digitalization has played a significant role in supporting economic, social, and environmental sustainability in villages. The main study using a society-centered approach found that, in general, sustainable development heavily relies on the active participation of the community and the strategic role of the village government in building collective awareness of change. The results of this article's study successfully revealed that the collective awareness of rural communities towards digitalization does not form naturally, but must be built through the active role of village governments as facilitators of change who understand the social context and local values.